A Multi-Disciplinary Approach in the Management of Endo-Perio Lesions: A 4-year Follow-Up Case Report - Stephani Dwiyanti (Case Reports in Dentistry)
Summary. This case report discusses the multi-disciplinary approach and long-term follow-up of a 66-year-old male who suffered a combined endodontic–periodontal lesion (EPL). As EPL is uncommon in daily practice and dentists’ knowledge and awareness of EPL is quite low, this case becomes of high interest and value to document and research. The objective of this study is to present the diagnosis, multi-disciplinary approach, and long-term follow-up of compromised teeth with EPL. It highlights the importance of the identification and elimination of all causative factors as well as the correct treatment sequence to achieve a predictable outcome. The patient was referred to the periodontist after multiple unsuccessful attempts by his previous dentist. He complained of recurrent dull pain and abscess on his upper left tooth (tooth #26) that had been present for the past three years. A diagnosis of combined EPL was obtained after thorough anamnesis, clinical evaluation, and radiographic examination. The clinician identified several predisposing factors, such as plaque, trauma from occlusion, and excessive force on tooth #26 due to incorrect denture design. Treatment involved multiple dental specialties. At the periodontist, the patient underwent scaling, root planning, and removal of overhanging part of the restoration. At the endodontist, root canal treatment (RCT) was completed. Two months after RCT, a periodontal regenerative procedure was done. The defect was filled with a combination of allograft/alloplastic bone graft and covered with a barrier membrane. Upon healing, the prosthodontist did the final restoration of fiber post with a metal crown on tooth #26 and constructed a new denture with a periodontal-friendly design. A follow-up at five months and four years showed excellent results. The patient was symptom-free, and tooth #26 showed no periodontal inflammation. Radiographic examination showed a good bone fill at the defect. Supportive periodontal therapy should be emphasized to achieve the long-term success of EPL.